Bala nço sobre a re forma Agrária bras ile ira nas duas últimas décadas - De Souza Esquerdo, Vanilde F.; Bergamasco, Sonia M. P. P. [UNESP] (My University, 2013)
La reforma agraria posibilita la desconcentración de las tierras y le da oportunidad a los trabajadores rurales para que desarrollen sus proyectos de vida, rescatando la dignidad de una población historicamente excluida. La conquista de la tierra posee significados que van desde el rescate de la ciudadanía hasta la mejora de la condición de vida por la adquisición de bienes, productos y servicios. Se observa que en Brasil todavía hay una fuerte concentración latifundiaria. En ese sentido, este trabajo tuvo por objetivo analizar el proceso de reforma agraria brasilera durante las dos últimas décadas. En ese período el país tuvo tres gobernantes, dos de ellos electos con el apoyo The agrarian reform allows for land redistribution and gives rural workers the opportunity to develop their life projects, rescuing the dignity of a historically excluded population. The conquest of the land carries significances that span from the rescue of citizenship to the improvement of living conditions due to the acquisition of goods, products and services. It is pointed out that in Brazil there still exists a marked concentration of large-landed estates. In this sense, this work had the objective of analyzing the Brazilian agrarian reform process during the last two decades. In this period the country had three Presidents, two of them elected with the support of the Rural Landless Workers Movement, increasing the expectations in relation to the fulfillment of the agrarian reform. The advances in the policies of rural settlements are notable; however, the structure of large-land estates remains unaltered. In the last two years (2011 and 2012) the number of settled families, as well as the number of settlements accomplished, were the worst since 2006. The priority of the current government is the eradication of extreme poverty and, in this sense, the agrarian reform becomes an essential policy to contribute to such goal, since with the distribution of the property of the land also diminishes the concentration of wealth.
Outcome of the Agrarian reform in Brazil during the last two decades